2019
DOI: 10.1136/tsaco-2019-000343
|View full text |Cite
|
Sign up to set email alerts
|

Early increase in anti-inflammatory biomarkers is associated with the development of multiple organ dysfunction syndrome in severely injured trauma patients

Abstract: BackgroundAs a result of improvements in the early resuscitation phase of trauma, mortality is largely driven by later mortality due to multiple organ dysfunction syndrome (MODS), which may be mediated by an early overdrive in the host immune response. If patients at risk for MODS could be identified early, preventive treatment measures could be taken. The aim of this study is to investigate whether specific biomarkers are associated with MODS.MethodsMultiple trauma patients presenting to the Amsterdam Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Identification of early biological signatures to predict development, progression, and clinical outcome of severe inflammation-mediated immune dysfunction is critical for timely intervention and mitigation of downstream effects. Prior research efforts have largely focused on individual or small numbers of classic systemic inflammatory markers as biological signatures [ 4 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ]. A combinatorial signature involving genome-wide multi-plexed analyses of interlinked pathways may have a greater predictive value at any given point.…”
Section: Inflammation and The Role Of Exosomal Cargomentioning
confidence: 99%
“…Identification of early biological signatures to predict development, progression, and clinical outcome of severe inflammation-mediated immune dysfunction is critical for timely intervention and mitigation of downstream effects. Prior research efforts have largely focused on individual or small numbers of classic systemic inflammatory markers as biological signatures [ 4 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ]. A combinatorial signature involving genome-wide multi-plexed analyses of interlinked pathways may have a greater predictive value at any given point.…”
Section: Inflammation and The Role Of Exosomal Cargomentioning
confidence: 99%
“…To date,despite enhanced understanding of MODS pathogenesis,there have been no effective therapy,and prevention is still crucial for MODS [4] .Therefore,early identi cation of multiple trauma patients who were at risk of developing MODS can help to timely prevention and intervention,and may improve these patient's prognosis.Recently studies showed several speci c biomarkers could be useful in predicting high risk patients to develop posttraumatic MODS.A study by Haasper [5] showed procalcitonin(PCT) had a high sensitivity for predicting the development of MODS(sensitivity was 0.88).Kleinveld [6] found that the combination of anti-in ammatory proteins interleukin 1receptor antagonist(IL-1RA) and Clara cell protein 16(CC-16) was most strongly associated with the development MODS by multivariate analysis.A retrospective cohort study [7] showed plasma levels of Neutrophil gelatinase-associated lipocalin(NGAL), paracrine osteoprtegerin(OPG) and IL-6 were signi cantly elevated in MODS+ group,and these biomarkers positively correlated with MODS score and diagnosis of MODS.Kong et al [8] found that delta neutrophil index (DNI)values of >3.25% and >5.3% at 12h post-admission were signi cant predictors of the development of MODS and 30-days mortality,respectively,in trauma patients.In addition,the AUC of combined detection of NF-κB 1.20,IL-6 25.1 ug/L and TNF-α 2.20 ng/ml in peripheral blood in predicting MODS was 0.853,95%CI(0.659,0.977) [9] . These above speci c biomarkers had a certain guiding signi cance for predicting developing of MODS in patients with multiple trauma.However,these biomarkers were not routinely performed in clinical particularly in emergency room,because of cumbersome laboratory techniques or high cost associated with these approaches currently inhibited their clinical implementation.Therefore,it is quite necessary to explore a easy-to-use and reliable predictive model for MODS following multiple trauma patients.…”
Section: Introductionmentioning
confidence: 99%